A novel template-free synthesis of Na-A Zeolite for enhanced removal of heavy metals from aqueous solutions - Mutairah S. Alshammari; Maryam AL_nosairy; Mha Albqmi; Hussein M. Ahmed; Adel M.A. Elhdad (PLoS ONE, 2026)
The removal of toxic heavy metals from wastewater remains a major environmental challenge due to their non-bio-degradability, persistence, and adverse health effects. In this work, a novel DES-assisted microwave hydrothermal route was developed for the rapid synthesis of hierarchical Na A. zeolite (NaAZ), offering a new pathway toward enhanced adsorption performance. Structural characterization (X-ray diffraction (XRD), SEM, Fourier Transform Infrared Spectroscopy” (FT-IR(Brunauer-Emmett-Teller method (BET) Scanning Electron Microscopy (SEM), Dispersive X-ray spectroscopy (EDX) confirmed the formation of highly crystalline cubic NaAZ with improved surface area and accessible porosity. Batch adsorption experiments were conducted to evaluate the uptake of Pb 2 ⁺ , Cu 2 ⁺ , Cd 2 ⁺ , Ni 2 ⁺ , and Zn 2 ⁺ ions under varying operational conditions, including contact time, adsorbent dose, initial concentration, pH, and temperature. Results showed fast adsorption kinetics, with equilibrium reached within 90 min for most ions. Kinetic modeling revealed that the pseudo-second-order model best described the process, while equilibrium data were well-fitted to the Langmuir isotherm, indicating monolayer adsorption. Thermodynamic parameters confirmed the spontaneous and endothermic nature of the adsorption. Fixed-bed column studies demonstrated efficient dynamic adsorption, with breakthrough behavior successfully modeled using Thomas, Yoon–Nelson, and Bohart–Adams equations, confirming the material’s suitability for continuous treatment applications. Furthermore, the synthesized NaAZ exhibited excellent regeneration and reusability, maintaining high removal efficiency over multiple cycles. Compared to conventional adsorbents such as activated carbon, graphene oxide, chitosan composites, bio-char, and natural zeolite. The superior adsorption performance and distinct selectivity pattern observed for NaAZ (Pb 2 ⁺ > Cu 2 ⁺ > Cd 2 ⁺ > Zn 2 ⁺ > Ni 2 ⁺) can be attributed to the synergistic effects of its hierarchical porosity and defect-engineered active sites, rather than simple ionic size or hydration radius considerations. The results indicated that the high efficiency of NaAZ was significantly for the removal of heavy metals from synthetic solutions, Overall, the optimal conditions with a contact time of 120 min, a pH of 6.0, temperature 35 0 C and an adsorbent dose of 250 mg.